Numerical modelling and design of hybrid cold-formed steel wall panels. (December 2020) - Usefi, Nima; Ronagh, Hamid; Sharafi, Pezhman
Abstract: Hybrid cold-formed steel (CFS) wall panel, composed of square hollow sections (SHS) and CFS open sections, can offer some great advantages with respect to the lateral performance of light steel frames, in particular for applications in mid-rise construction. This paper presents non-linear finite element modelling of hybrid wall panels, calibrated through experimental tests, and their applications to different designs. The study involves the lateral behaviour of the proposed hybrid walls in terms of load-displacement curve, failure mode, stiffness, ductility ratio, energy absorption, and strength to weight ratio. First, a numerical model, verified and calibrated based on the experimental tests on the hybrid wall panels, is presented. Thereafter, using the validated numerical model, twenty new hybrid wall panel designs are proposed in order to investigate the effect of different SHS brace configurations on the hybrid panels' performance. The comparison of the experimental and numerical results indicates that superior seismic performance can be achieved from the proposed hybrid CFS wall designs. Highlights: Effect of SHS truss skeleton on the lateral performance of the hybrid CFS panels is studied. Lateral performance of hybrid CFS walls with different configurations is numerically investigated. The proposed designs of hybrid CFS walls are suitable for application in mid-rise construction.